Gene Expression and Its Discontents The Social Production of Chronic Disease - Wallace, Rodrick; Wallace, Deborah; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
A cognitive paradigm for gene expression, via the asymptotic limit theorems of information theory, allows better understanding of how embedding context affects the development of organisms. In sum, epigenetic information sources act as tunable catalysts, directing ontogeny into characteristic pathways, a perspective having important implications for epigenetic epidemiology. The authors show how environmental stressors, in a large sense, can induce a broad spectrum of developmental dysfunctions, and examine a number of pandemic chronic diseases, using U.S. data at different scales on the effects of the legacy of slavery compounded by accelerating industrial and urban decay. Developmental disorders, broadly taken, are unlikely to respond to medical interventions in the face of serious, persistent individual and community stress. In particular, drugs powerful enough to affect deleterious epigenetic programming will likely trigger side effects leading to shortened lifespan. The address of pandemic chronic disease requires significant large-scale changes in public policy and resource allocation.
Models of development -- Groupoid symmetries -- Epigenetic catalysis -- Developmental disorders -- An interim perspective -- The obesity pandemic in the US -- Coronary heart disease in the US -- Cancer: a developmental perspective -- Autoimmune disorders -- Demoralization and obesity in Upper Manhattan -- Death at an early age: AIDS and related mortality in New York City -- Final thoughts -- Mathematical appendix -- References.
Keywords: Medicine; Human genetics; Epidemiology; Bioinformatics; Biomedicine; Human Genetics; Computational Biology/Bioinformatics.; Public Health/Gesundheitswesen.; Epidemiology